Value of Ralgro® implants in feedlot steers previously maintained on a high endophyte-infected fescue hay - L.R. Corah; F.K. Brazle; Frank Blecha; P.G. Reddy; R.E. Jr. Wary; J. Klindt (Kansas Agricultural Experiment Station Research Reports, 1990)
Steers previously fed high-endophyte fescue hay showed a greater response of Ralgro® implants than those fed a low-endophyte hay. The mode of action for this response was not explained by cellular immune system responses or variability in prolactin levels.
Keywords: Cattlemen& #x27; s Day; 1990; Kansas Agricultural Experiment Station contribution; no. 90-361-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 592; Beef; Stockers; Finishing; Endophyte; Fescue; Ralgo